Micro-dose of resistance-exercise: effects of sub-maximal thumb exertion on leukocyte redistribution and fatigue in trained male weightlifters - Szlezak, A. M.; Lotti, T.; Keane, J.; Szlezak, S. L.; Minahan, C. (Journal of Physical Education and Sport, 2015)
This study examined the effect of a micro-dose of thumb resistance-exercise on leukocyte redistribution, thumb pinch-strength and reported fatigue. The effect of training status was also studied. 30 male participants (20 weightlifting-trained; 10 untrained) were separated into 3 groups of 10 (WLEXP; UTEXP; WLPLA) & performed 4 x60 second thumb isometric resistance-exercise intervals separated by 60 second rest intervals in a single-blinded placebo-controlled study. Participants were assessed over a 60 minute post-intervention recovery period. Pinch-strength decreased in WLEXP and UTEXP groups (p<0.01), and recovered to baseline values (p=0.01) in the WLEXP group only. Fatigue increased in WLEXP and UTEXP groups and remained elevated across time (p<0.01). Circulating total leukocyte and lymphocyte counts increased in WLEXP and UTEXP groups across time. Constant elevation was seen in both measures for the UTEXP group (p<0.05) whereas the WLEXP group showed two peaks in leukocyte (baseline - 0 mins post, p<0.01; 20 - 60 mins post, p=0.02) and lymphocyte counts (base-line - 0 mins post, p<0.01; 20 - 60 mins post, p<0.01). Monocyte count increased similarly from baseline (p=0.47) in the WLEXP group (p=0.02) and UTEXP group (p<0.01) at 60 minutes post. Our results suggest that perception of fatigue does not correlate with physiological recovery from thumb resistance-exercise in resistance-trained individuals which has implications for recovery monitoring. Of particular novelty, we also showed that a micro-dose of thumb resistance-exercise is sufficiently stressful to distort leukocyte trafficking and thus homeostasis.